Развитие инструментария алгебры алгоритмики с целью разработки параллельных программ с использованием эвристических средств - Дорошенко, А.Е.; Котюк, Н.В.; Николаев, С.С.; Цейтлин, Г.Е.; Яценко, Е.А. (Кибернетика и системный анализ, 2010)
Розглянуто розвиток алгеброалгоритмічного інструментарію для конструювання паралельних алгоритмів на основі спільного використання алгеброалгоритмічної методології специфікації і розробки програм та неалгоритмічних (евристичних) методів генерації коду. Евристичною частиною системи є динамічне налаштування програмного коду на цільову платформу і його оптимізація з використанням генерації коду, що самонавчається, і евристичних технологій. The paper proposes a new approach and a system to develop parallel algorithms based on the joint use of the algebraic-algorithmic methodology of specification and development and non-algorithmic (heuristic) techniques for code generation. The algebraic part of the methodology provides the formalized process of parallel program design through high-level algebra-algorithmic specifications and automating transformations up to program code in a standard programming language. The heuristic part of the system stands for dynamical adjustment of program code for a target platform and its optimization using self-learning code generation and heuristic technologies.